A Critical Response to Kevin Stenson's Governing the Local: Sovereignty, Social Governance and Community Safety - Robert P. Fairbanks (Social Work & Society, 2008)
In his compelling case study of local governance and community safety in the UK Thames Valley, Kevin Stenson makes several important contributions to the field of governmentality studies. While the paper's merits are far-reaching, to this reader's assessment they can be summarized in the following key areas: 1) Empirically, the article enhances our knowledge of the political economic transformation of a region otherwise overlooked in social science research [1] ; 2) Conceptually, Stenson offers several theoretical and analytical refrains that, while becoming increasingly commonplace, are nonetheless still germane and rightly oriented to offer push back against otherwise totalizing, reified accounts of roll back/roll out neoliberalism. A welcomed new approach is offered as a corrective, The Realist Governmentality perspective, which emphasizes the interrelated and co-constitutive nature of politics, local culture, and habitus in processes related to the restructuring of social governance; 3) Methodologically, the paper makes a pitch for the ways in which finely grained, nuanced, mixed-method/ethnographic analyses have the potential to further problematize and recast a field of governmentality studies far too often dominated by discursive and textual approaches.